Genetically Determined Risk of Depression and Functional Outcome After Ischemic Stroke: Mendelian Randomization Study. Issue 8 (August 2019) - Gill, Dipender; James, Nicole E.; Monori, Grace; Lorentzen, Erik; Fernandez-Cadenas, Israel; Lemmens, Robin; Thijs, Vincent; Rost, Natalia S.; Scott, Rodney; Hankey, Graeme J.; Lindgren, Arne; Jern, Christina; et al.
Abstract : Background and Purpose—: Psychosocial factors can have implications for ischemic stroke risk and recovery. This study investigated the effect of genetically determined risk of depression on these outcomes using the Mendelian randomization (MR) framework. Methods—: Genetic instruments for risk of depression were identified in a discovery genome-wide association study of 246 363 cases and 561 190 controls and further replicated in a separate population of 474 574 cases and 1 032 579 controls. Corresponding genetic association estimates for risk of ischemic stroke were taken from 60 341 cases and 454 450 controls, with those for functional outcome 3 months after ischemic stroke taken from an analysis of 6021 patients. Following statistical power calculation, inverse-variance weighted MR was performed to pool estimates across different instruments. The Cochran Q heterogeneity test, weighted median MR, and MR pleiotropy residual sum and outlier were used to explore possible bias relating to inclusion of pleiotropic variants. Results—: There was no MR evidence for an effect of genetically determined risk of depression on ischemic stroke risk. Although suffering low statistical power, the main inverse-variance weighted MR analysis was suggestive of a detrimental effect of genetically determined risk of depression on functional outcome after ischemic stroke (odds ratio of poor outcome [modified Rankin Scale, ≥3] per 1-SD increase in genetically determined risk of depression, 1.81; 95% CI, 0.98–3.35; P =0.06). There was no evidence of heterogeneity between MR estimates produced by different instruments (Q P =0.26). Comparable MR estimates were obtained with weighted median MR (odds ratio, 2.57; 95% CI, 1.05–6.25; P =0.04) and MR pleiotropy residual sum and outlier (odds ratio, 1.81; 95% CI, 0.95–3.46; P =0.08). Conclusions—: We found no MR evidence of genetically determined risk of depression affecting ischemic stroke risk but did find consistent MR evidence suggestive of a possible effect on functional outcome after ischemic stroke. Given the widespread prevalence of depression-related morbidity, these findings could have implications for prognostication and personalized rehabilitation after stroke. Abstract : Supplemental Digital Content is available in the text.